Meningkatkan Kecakapan Berbicara Melalui Pidato Bahasa Inggris pada Siswa SMP di Pulau Moa - Louisa Sarah Kamanasa; Fredi Meyer; Rosina F. J. Lekawael; Marcy Ferdinandus; Erna Keiwury; Crisendy Mahaaly (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This activity aims to train junior high school students on Moa Island, Southwest Maluku Regency, Maluku Province to develop their speaking skills through Speech activities. This is a response to the importance of one of the four English skills: listening, speaking, reading, and writing. By carrying out this activity, students can develop their speaking skills.